Studeny Spoj - Remo, Miro (Slovakia : Badac, Peter, 2007)
“Ill emotions” are omnipresent and acting just like any regular lethal disease they absorb slowly. Piling up in parents‘ souls, little by little it searches for a way to break through the child’s immunity until they find themselves absorbed in the world controlled by cold, ill-functioning joints, relationships in fact. The main protagonist is an eleven-year-old girl born into a low-class family. Raised in the harsh conditions of industrial surroundings, the little girl eventually comes to terms with the grave emotional condition her family is faced with.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films